(untitled) (Revista Lusófona de Educação, 2025)
There is currently widespread recognition of the important role that writing should occupy in higher education. Given the necessity of placing this activity at the center of educational policies and taking implicit theories as a reference, the main objective of this study was to explore university students’ beliefs about writing. Through a content analysis of compositions written by 264 participants, the main findings indicate that many students still believe, either globally or partially, that writing is a talent independent of effort. Given the influence that beliefs have on performance, we conclude that higher education curricula should incorporate the development of writing skills and consider how students perceive the writing process.